Radical Subjects in Nawal El-Sa’adawi’s Novel “Woman at Point Zero” : A Study of Slavoj Zizek’s Subjectivity - Pringadie, Lorraine Aisyah Prihatiningtyas (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Feminism, patriarchy, power, and power relations are part of the symbolic world according to Slavoj Zizek's concept and theory of subjectivity. This study uses this theory to describe the subjectivity of Firdaus, the main character in the novel Perempuan di Titik Nol by Nawal El-Sa’adawi. In this theory, Zizek defines the subject through his actions in the symbolic world or ideological world. The method used in this study is descriptive analysis, which describes the subject's radical actions from the results of his behavioral analysis according to Zizek's theory of subjectivity. In this theory, Zizek introduces the concept of the symbolic world, cynicism, the moment of emptiness, and radical action. Through these concepts, this study concludes that the main character in this novel is a radical subject. Although continuously trapped from one symbol to another, in the end the subject can release the symbols and ideological traps from within himself. The radical actions taken by the subject make the subject feel full or become an authentic subject. Namely a subject who wants nothing and is not afraid of anything, even death.